Alum Pickering Emulsion as Effective Adjuvant to Improve Malaria Vaccine Efficacy - Qiuting Chen (MDPI AG, 2021)
Malaria is a life-threatening global epidemic disease and has caused more than 400,000 deaths in 2019. To control and prevent malaria, the development of a vaccine is a potential method. An effective malaria vaccine should either combine antigens from all stages of the malaria parasite’s life cycle, or epitopes of multiple key antigens due to the complexity of the Plasmodium parasite. Malaria’s random constructed antigen-1 (M.RCAg-1) is one of the recombinant vaccines, which was selected from a DNA library containing thousands of diverse multi-epitope chimeric antigen genes. Moreover, besides selecting an antigen, using an adjuvant is another important procedure for most vaccine development procedures. Freund’s adjuvant is considered an effective vaccine adjuvant for malaria vaccine, but it cannot be used in clinical settings because of its serious side effects. Traditional adjuvants, such as alum adjuvant, are limited by their unsatisfactory immune effects in malaria vaccines, hence there is an urgent need to develop a novel, safe and efficient adjuvant. In recent years, Pickering emulsions have attracted increasing attention as novel adjuvant. In contrast to classical emulsions, Pickering emulsions are stabilized by solid particles instead of surfactant, having pliability and lateral mobility. In this study, we selected aluminum hydroxide gel (termed as “alum”) as a stabilizer to prepare alum-stabilized Pickering emulsions (ALPE) as a malaria vaccine adjuvant. In addition, monophosphoryl lipid A (MPLA) as an immunostimulant was incorporated into the Pickering emulsion (ALMPE) to further enhance the immune response. In vitro tests showed that, compared with alum, ALPE and ALMPE showed higher antigen load rates and could be effectively endocytosed by J774a.1 cells. In vivo studies indicated that ALMPE could induce as high antibody titers as Freund’s adjuvant. The biocompatibility study also proved ALMPE with excellent biocompatibility. These results suggest that ALMPE is a potential adjuvant for a malaria vaccine.